A „másik realitás” regénye: Szerb Antal: Utas és holdvilág - Takács, László (Studia Litteraria, 2022)
The circle of artists and scholars, organized around the classical philologist Károly Kerényi, occupies a special place in the intellectual life of Hungary in the 1930s. Antal Szerb, one of the most talented essayists and writers of the interwar period, also belonged to this group of friends. Szerb was heavily influenced by Kerényi’s views on ancient Greek religion and classical literature. In 1936, the writer published his analysis of the latest Western European and American novels, entitled Everyday Life and Miracles, which is partly a prelude to his 1937 novel Journey by Moonlight. e novel features a caricature of Kerényi, while the plot is in many respects a special blend of a recipe filtered from contemporary novels and ancient literary products.